1996
DOI: 10.3109/02844319609062810
|View full text |Cite
|
Sign up to set email alerts
|

Contact Hypersensitivity is Suppressed After Sensitisation by Dinitrofluorobenzene of Early Stage Iso-Skin Grafts

Abstract: Isologous free skin grafts were applied to the backs of BALB/c mice and contact hypersensitivity studied by epicutaneous application of DNFB (2,4-dinitro-1-fluorobenzene) to the grafted skin. In the first experiment, the grafted skin was sensitised and the elicitation reaction assessed by measuring the ear swelling after five days. Sensitisation was not successful until two weeks after grafting. In such non-responding animals, re-sensitisation with DNFB on the ungrafted skin area was also unsuccessful, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…To confirm the previous observation by Yasuda et al (1996) and to further examine whether the suppression of CHS by sensitization through skin grafting is a local or systemic phenomenon, mice were sensitized with picryl chloride (PCl) through grafted dorsal skin or non-grafted abdominal skin after skin graft implementation (on day 7 after operation). When PCl was applied to the grafted area for sensitization, the ear swelling challenge response was significantly lower than that of the positive control without skin graft (Figure 1).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…To confirm the previous observation by Yasuda et al (1996) and to further examine whether the suppression of CHS by sensitization through skin grafting is a local or systemic phenomenon, mice were sensitized with picryl chloride (PCl) through grafted dorsal skin or non-grafted abdominal skin after skin graft implementation (on day 7 after operation). When PCl was applied to the grafted area for sensitization, the ear swelling challenge response was significantly lower than that of the positive control without skin graft (Figure 1).…”
Section: Resultsmentioning
confidence: 85%
“…Clinical observations have suggested impaired immunity in grafted skin (Doiurnon et al, 2001), and the lack of dermatitis on the graft is empirically known; therefore, some immunological alterations are thought to take place in the graft. Only one study has demonstrated that murine contact hypersensitivity (CHS) to a hapten cannot develop upon sensitization through full-thickness grafted skin (Yasuda et al, 1996).…”
Section: Introductionmentioning
confidence: 99%